1962
DOI: 10.1103/physrev.125.606
|View full text |Cite
|
Sign up to set email alerts
|

Excitation Functions for Heavy-Ion-Induced Reactions on Aluminum-27

Abstract: Excitation functions for a number of C 12 -, N 14 -, and 0 16 -induced reactions on aluminum-27 have been studied using stacked-foil techniques and the ion beams of the Yale Heavy Ion Accelerator. The yields of CI 34 -38 , P 32 , Al 28 -29 , Mg 27 , Na 24 , and F 18 have been measured in the energy range from 10.5 to about 1 Mev per nucleon. The production of the radionuclides Cl 34 > 38 , P 32 , and in the case of C 12 irradiation Al 28 , are due to evaporation processes from a compound-nucleus system, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Since the mass number of residue 24Na is very close to mass of the target 27A1, the production of residues 24Na are due to the direct reaction mechanism by stripping of two protons and one neutron from the target nucleus as pointed out by Landenbauer-Bellis et al [25]. The SUMRULE model predictions for the present system concludes that ICF is associated even at smaller values than that of the critical value of the angular momentum for CF process.…”
Section: Analysis With Sumrule Modelmentioning
confidence: 68%
See 4 more Smart Citations
“…Since the mass number of residue 24Na is very close to mass of the target 27A1, the production of residues 24Na are due to the direct reaction mechanism by stripping of two protons and one neutron from the target nucleus as pointed out by Landenbauer-Bellis et al [25]. The SUMRULE model predictions for the present system concludes that ICF is associated even at smaller values than that of the critical value of the angular momentum for CF process.…”
Section: Analysis With Sumrule Modelmentioning
confidence: 68%
“…3 along with pace4 calculations. The measured values of cross sections by Landenbauer-Bellis et al [25], having large uncertainties in the energy, are also shown in Fig. 3 for comparison.…”
Section: Analysis Of Ef With Code Pace4mentioning
confidence: 94%
See 3 more Smart Citations